2017
DOI: 10.1097/md.0000000000008557
|View full text |Cite
|
Sign up to set email alerts
|

Volume-based metabolic parameter of breast cancer on preoperative 18F-FDG PET/CT could predict axillary lymph node metastasis

Abstract: The purpose of our study was to evaluate the association between metabolic parameters on FDG PET/CT and axillary lymph node metastasis (ALNM) in patients with invasive breast cancer.From January 2012 to December 2012, we analyzed 173 patients with invasive ductal carcinoma (IDC) who underwent both initial breast magnetic resonance imaging (MRI) and 18F-fluorodeoxyglucose positron emission tomography/computed tomography (FDG PET/CT) examinations. All metabolic parameters were measured from the tumor volume segm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(13 citation statements)
references
References 29 publications
1
11
1
Order By: Relevance
“…Several studies proved that the SUVmax of primary tumor was significantly higher in cases with high nuclear grade tumors similar to ours [32,33].ALNs metastasis is considered the most important prognostic factor in the BC . Patients with positive ALNs had significantly higher median SUVmax values similar to several studies [35,41]. Larger tumors contain more tumor cells than the smaller ones , thus requiring a greater glucose supply to maintain the metabolism and proliferation of tumor cells, which would result in an increase in SUVmax.…”
Section: Discussionsupporting
confidence: 81%
“…Several studies proved that the SUVmax of primary tumor was significantly higher in cases with high nuclear grade tumors similar to ours [32,33].ALNs metastasis is considered the most important prognostic factor in the BC . Patients with positive ALNs had significantly higher median SUVmax values similar to several studies [35,41]. Larger tumors contain more tumor cells than the smaller ones , thus requiring a greater glucose supply to maintain the metabolism and proliferation of tumor cells, which would result in an increase in SUVmax.…”
Section: Discussionsupporting
confidence: 81%
“…Their analysis showed that SUVmax and TLG were not significantly predictive of survival, yet MTV was significant. A similar study concluded that MTV may be associated with axillary lymph node status in breast cancer patients, particularly in T2 and T3 stages 6 . Another study by Hyun et al .…”
Section: Discussionmentioning
confidence: 71%
“…Volumetric PET parameters including the metabolic tumor volume (MTV) and total lesion glycolysis (TLG) have also taken on greater importance in prognostic prediction over SUV parameters [ 48 , 49 ]. In breast cancer, the MTV may be associated with axillary lymph node metastasis and overall survival [ 50 – 52 ]. In addition, TLG can be used to predict event-free survival [ 53 ].…”
Section: Discussionmentioning
confidence: 99%